Ciprofloxacin‐loaded keratin hydrogels reduce infection and support healing in a porcine partial‐thickness thermal burn. Issue 4 (23rd June 2016) - Roy, Daniel C.; Tomblyn, Seth; Isaac, Kameel M.; Kowalczewski, Christine J.; Burmeister, David M.; Burnett, Luke R.; Christy, Robert J.
Abstract: Infection is a leading cause of morbidity and mortality in burn patients. Current therapies include silver‐based creams and dressings, which display limited antimicrobial effectiveness and impair healing. The need exists for a topical, point‐of‐injury antibiotic treatment that provides sustained antimicrobial activity without impeding wound repair. Fitting this description are keratin‐based hydrogels, which are fully biocompatible and support the slow‐release of antibiotics. Here we develop a porcine model of an infected partial‐thickness burn to test the effects of ciprofloxacin‐loaded keratin hydrogels on infection and wound healing. Partial‐thickness burns were inoculated with either Pseudomonas aeruginosa or Methicillin‐resistant Staphylococcus aureus, resulting in infections that persisted for >2 weeks that exceeded 10 5 and 10 6 cfu per gram of tissue, respectively. Compared to silver sulfadiazine, ciprofloxacin‐loaded keratin hydrogel treatment significantly reduced the amount of P. aeruginosa and S. aureus in the burn by >99% on days 4, 7, 11, and 15 postinjury. Further, burns treated with ciprofloxacin‐loaded keratin hydrogels exhibited similar healing patterns as uninfected burns with regards to reepithelialization, macrophage recruitment, and collagen deposition and remodeling. The ability of keratin hydrogels to deliver antibiotics to fight infection and support healing of partial‐thickness burns make them a strong candidate as a first‐line burn therapy.